ERROR ANALYSIS IN CLAUSE USAGE OF BAHASA INDONESIA IN CHAPTER ONE OF THE THESIS BY A PBSI STUDENT AT UNMUS “ANALISIS KARAKTER TOKOH UTAMA DALAM FILM A STREET CAT NAMED BOB BY ROGERS SPOTTISWOODE” BY YOLENTA OKTOVIA MAHUZE - Ekfindar Diliana (PT Akselerasi Karya Mandiri, 2024)
The focus of this study is the errors in the clause usage in chapter one in student’s thesis majoring Indonesian Language and Literature Education at Musamus University–